Vasoconstrictor agonists activate G-protein-dependent receptor-operated calcium channels in pig aortic microsomes. - Blayney, L M (1992)
Receptor-operated Ca2+ channels were characterized by their ability to decrease steady-state ATP-dependent Ca2+ accumulation into pig aortic microsomes. The vasoconstrictor agents noradrenaline, angiotensin II and adenosine 5'-[alpha beta-methylene]triphosphate (pp[CH2]pA) all decreased Ca2+ accumulation only when sonicated into vesicles (to allow access to receptor sites) and in the presence of guanosine 5'-[beta gamma-imido]triphosphate to activate transducing G-proteins. The effect of noradrenaline was inhibited by the alpha 2 antagonist yohimbine, but not by the alpha 1 antagonist prazosin. The effect of none of the agonists was reversed by diltiazem. SK&F 96365 (an inhibitor of receptor-mediated Ca2+ influx into intact cells) reversed the effect of noradrenaline, but not that of pp[CH2]pA, which suggests that at least two receptor-operated channels may be present in this preparation.